PREHOSPITAL CARE SIMULATION IMPROVES SELF-EFFICACY AND TRAFFIC ACCIDENT FIRST AID SKILLS - Afni, Anissa Cindy Nurul; Saputro, Sutiyo Dani; Barros, Carmelita (SYNTHESIS Global Health Journal, 2024)
Background. Inappropriate actions when prehospital care for traffic accidents often lead to new injuries or death. The public needs to be trained in traffic accident first aid. To increase the self-efficacy and skills of the community to provide help appropriately, quickly, and accurately. This study aim was to determine the effect of prehospital care simulation on people's self-efficacy and skills in first aid for traffic accidents Research Method. This research was quantitative, Quasy experiment with pre and post-tests without a control group. The population was all adolescents of Waru Village, Karanganyar Regency, Indonesia, consisting of 78 people, with total sampling. The instruments used a self-efficacy questionnaire and checklist instructions for first aid skills in traffic accidents. Data analysis used the Wilcoxon test. Findings. The results showed that pre-hospital simulation of traffic accidents has an influence on adolescent self-efficacy in providing first aid for traffic accidents with a p-value was 0.000. The results showed that pre-hospital simulation of traffic accidents has an influence on adolescent skills in providing first aid for traffic accidents with a p-value of Skills 0.000. Conclusion. There is a difference between before and after prehospital care simulation on adolescents' self-efficacy and skills in first aid for traffic accidents. They try actively and get feedback from the actions taken, thus creating new experiences that affect their self-efficacy.